(3JQLeI Jbj GdOjf GdSHcj(B((3Ydj Hf YHOGdcGaj(B)s - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s ((3eMeO Hf YHOGdbGOQ GdTgQRhQi GdehUdj s)
(3ChdgG (B:s
(3hHYO agPg JQLeI TQjaI ChQOgG YHOGdhgGH GdSHcj ai GdWHbGJ GdcHQi bGd Ydi Hf YHOGdcGaj s
(3BNQgG (B:s
(3hfMf Ydi jbjf HCf ajge ef gh GYdi ef GdTjN GdEeGe s
(3GdeDda hdO GdSHcj GdeJQLe dgs
(3eCNhPI ef cJGHg WHbGJ GdTGaYjI GdcHQis
(3JedcgG GHf GdeHdW GdTGaYj SfI (B986 (3g`s
(3hCMeO QGLj GHf eMehO SfI (B1294(3g`s
(3hHBNQgG SeGYGJ Ydi GdeDda s
(3bQf GdfSN (B:s
Keywords: (3GdJGQjNs